Effects of food safety recalls on a firm's shareholder value - Teague, Laura (Kansas State University, 2013)
This study focuses on the effects of food safety recalls on a firm’s shareholder value. In this study, the effects of six recalls are studied using the event study method. Three models were used involving the daily stock returns for each recall, the daily prices from the S&P 500 and the S&P 500-Packaged Foods and Meats prices. Each of these models was used to determine the abnormal returns for the individual recalls during a determined event window. The four companies responsible for the recalls are all large, highly-diversified food production companies. Overall, the results from this study show there is short-term effect on shareholder values for the companies included in this study. This is an important topic that was widely studied in the late 1990’s and early part of the 2000’s. There have not been any notable studies in this area in the past decade which is why this study is useful. Results of this study are comparable to those mentioned in the literature review section.
Keywords: Abnormal return; Food safety recalls; Shareholder value; Economics, Agricultural (0503)